The relationship between platelet-to-lymphocyte ratio and pulmonary embolism severity in acute pulmonary embolism - Telo, Selda; Kuluozturk, Mutlu; Deveci, Figen; Kirkil, Gamze (Edizioni Minerva Medica, 2019)
Background: The aim of this study was to determine the level of platelet-to-lymphocyte ratio (PLR) and neutrophil-to-lymphocyte ratio (NLR) in patients with acute pulmonary embolism (APE) according to high and low risk for early mortality based on simplified Pulmonary Embolism Severity Index (sPESI). In addition, it was investigated the relationship between PLR and NLR with systolic pulmonary artery pressure (sPAP), cardiac markers, disease severity and hospital, 1th month, 3th month and 3-month total mortality. Methods: Our hospital's electronic patient database was searched for the patients with APE during last year and eighty-two patients retrospectively evaluated. Plasma D-dimer, troponin I (TnI), brain natriuretic peptide (BNP), hemogram values, sPAP from echocardiographic findings were recorded from database system. Hospital mortality was determined from files of cases and 1th, 3th month mortality and survival information were determined by phone calls with the patient and/or relatives. Results: A percentage of 67.1% (55) of APE cases had sPESI >= 1. There was no significant difference for age and sex between high and low risk patients according to sPESI (P>0.05). The mean serum BNP, TnI, sPAP, neutrophil counts, platelet counts, PLR and NLR was statistically increased and lymphocyte counts was statistically decreased in high risk patients according to sPESI compared with low risk patients (P<0.01 for BNP, PLR and NLR; P<0.05 for TnI, sPAP, neutrophil and platelet; P<0.01 for lymphocyte). There was no significantly difference for hospital and total 3-month mortality between high and low risk patients (P> 0.05). When the cut-off value of PLO was taken as >= 156 by ROC analysis for the predicting of high sPESI, PLR had an area under the curve (AUC) in the receiver operating characteristic (ROC) curve of 0.704 (0.591-0.816; 95% CI; P<0.01) and the cut-off value of NLR was taken as >= 3.56 by ROC analysis for the predicting of high sPESI, NLR had an area under the curve (AUC) in the receiver operating characteristic (ROC) curve of 0.675 (0.556-0.794; 95% CI; P< 0.05). An NLR level of 3.56 was taken as the cut-off between high and low risk patients according to sPESI, NLR had a sensitivity of 66% and specificity of 53%. When the cases were evaluated as two groups according to the cut-off value of 156; total 3-month mortality was statistically increased (chi(2)= 6.896, P< 0.01) and when the cases were evaluated as two groups according to the based NLR cut-off value of 3.56; hospital mortality, 3th month mortality and total 3-month mortality was statistically increased (chi(2)= 4.771, P< 0.05;.2= 4.383, P< 0.05; chi(2)= 9.101, P< 0.01 respectively). Conclusions: PLR and NLR increased in patients with high risk, and PLR may have predicting value for 3-month mortality while NLR may have predicting value for hospital mortality, 3th month mortality and total 3-month mortality in patients with APE.
Keywords: Pulmonary embolism; Blood platelets; Lymphocytes